Analisa Pengetahuan PHBS pada Kader Posyandu Desa Tamanan Bondowoso dalam Upaya Penurunan Stunting Pada Balita - Muhammad Nurul Amin; Tecky Indriana; I Dewa Ayu Ratna Dewanti; Nurud Diniyah; Budi Yuwono; Agus Sumono; Roedy Budirahardjo; Banun Kusumawardani (Dental Agromedis, 2024)
Stunting in toddlers is related to growth and development disorders. One important factor in preventing stunting is the implementation of Clean and Healthy Living Behaviour (CHLB). CHLB plays a role in improving the nutritional and health status of children, as well as preventing various diseases that can contribute to stunting. The role of cadres is very important because cadres are responsible for implementing the posyandu program, are the main movers in promotive, preventive activities and are motivators for community members. The aim of this service is to analyse knowledge about PHBS among posyandu cadres in Tamanan Village, Tamanan District, Bondowoso Regency. The service method is an outreach activity aimed at providing knowledge about CHLB with the hope that people will change their behaviour to protect their health and the environment independently. Formative evaluation procedures in the form of pretest and posttest. Data were analyzed using descriptive analysis techniques. Continue with the normality test and paired sample t-test. The results obtained were that this community service activity was carried out on all posyandu cadres. Evaluation showed that there was a difference in the average test scores before and after the counselling. Providing counselling is able to provide changes in the knowledge of posyandu cadres which is marked by an increase in posttest scores which are higher compared to posttest scores. The conclusion is that the knowledge of Tamanan Bondowoso Village Posyandu cadres regarding CHLB in efforts to reduce stunting in toddlers can be increased through the counselling provided.Keywords: CHLB, counseling, posyandu cadres, stunting.